ANALYSIS OF PROTOCOLS IN CONNECTING IOT DEVICES TO THE NETWORK (Scientific journal of the Fergana State University, 2026)
This article presents a systematic analysis of protocols commonly used for connecting Internet of Things (IoT) devices to networks. The study examines lightweight and resource-constrained transport and application layer protocols such as MQTT, CoAP, and LwM2M, as well as LPWAN technologies designed for low-power wide-area networks, including LoRaWAN and NB-IoT. The paper compares the architectural features of the protocols, their impact on device resources, security mechanisms, and limitations in practical implementation. The analysis results provide a set of practical recommendations and criteria that should be considered when selecting appropriate protocols.